Experimental Research Methodologies in Organizational Behavior Management. Issue 2 (3rd April 2021) - Erath, Tyler G.; Pellegrino, Azure J.; DiGennaro Reed, Florence D.; Ruby, Sandra A.; Blackman, Abigail L.; Novak, Matthew D.
ABSTRACT: Organizational behavior management (OBM) is a scientific approach to understanding behavior and its relation to the workplace. As a natural science it relies on the use of sound experimental research methodology. This methodology has been critical to the field's success in demonstrating the application of behavioral principles across the basic–translational–applied continuum, from laboratory to natural workplace settings. The purpose of this paper is to present an overview of experimental methods commonly used within the field. We attempt to highlight the range and diversity of OBM research by providing examples of different approaches to research and design methodologies. In doing so, we review strengths, limitations, and examples of various single-case and group research designs.